(untitled) (Journal of Hama University, 2025)
Oil and gas sector is one of the industrial sectors that supposed to need scientific research to develop the exploration, drilling, production, processing and transportation operations carried out by this sector, and to find creative solutions to the continuous challenges it faces, thus contributing to the upgrading of this sector, which reflects positively on the economy as a whole. This research aims to determine the role of scientific research in solving the problems of the oil and gas sector in Syria and avoiding its obstacles from the point of view of its employees. The descriptive analytical method was used by designing a questionnaire and making sure of its truthfulness and consistency, and then applied to (214) workers at Hayan Petroleum Company (HPC). The results showed that there is a role for scientific research in the oil and gas sector in Syria from the point of view of its employees, in addition to the importance of scientific research in solving the problems of the oil and gas sector in Syria from the point of view of its employees to avoid the obstacles facing them. The results also showed that there are no differences between the opinions of HPC employees on the role of scientific research in solving the problems of the oil and gas sector depending on two variables (gender, nature of work), while there are differences between the opinions of HPC employees on the role of scientific research in solving the problems of the oil and gas sector depending on two variables (scientific qualification and years of experience).